High piezoelectric response in the new coexistent phase boundary of 0.87BaTiO3–(0.13-x)BaZrO3–xCaTiO3. (5th December 2015) - Sutapun, Manoon; Vittayakorn, Wanwilai; Muanghlua, Rangson; Vittayakorn, Naratip
Abstract: An investigation of the coexistent ferroelectric phase was carried out on the ternary system of 0.87BaTiO3 –(0.13- x )BaZrO3 – x CaTiO3 [abbreviated as BT–BZ– x CT (where 0.00 ≤  x  ≤ 0.13)]. Temperature-, frequency-dependent dielectric data, electric field-dependent strain and polarization as a function of composition are presented in order to understand the relationships of structure-properties and find the high piezoelectric response in this system. Results showed that ceramics in the composition range of 0.00 ≤  x  < 0.04 were of a rhombohedral structure and transformed into a tetragonal structure at x  > 0.06. The multiphase coexistence of the rhombohedral and tetragonal phase in this system was identified at x  = 0.06. A large, virtually hysteresis-free electric field induced strain of 0.23% was achieved with the composition, x  = 0.06, at 40 kV/cm on the boundary between rhombohedral and tetragonal phase. This relates to an extraordinarily high and normalized piezoelectric coefficient ( Smax / Emax ) of 1280 pm/V, which was reached at a low electric field applied at 10 kV/mm. These results indicated that a high piezoelectric response may stem primarily from the rhombohedral-tetragonal phase boundary, due to greater lattice softening and reduced energy barriers for polarized rotation. Graphical abstract: Highlights: The new coexistent phase composition in the 0.87BaTiO3 –(0.13- x )BaZrO3 – x CaTiO3 system was identified. A high normalized piezoelectric coefficient (Smax /Emax ) of 1260 pm/V was achieved at the coexistent phase composition. A composition–temperature ferroelectric phase diagram was proposed in this work.